Should low-wage workers care about where they work? Assessing the impact of employer characteristics on low-wage mobility - Nicole Guertzgen; Anja Heinze (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper studies the importance of employer-specific determinants in escaping low earnings in Germany. To address the initial conditions problem and the endogeneity of employer retention, we model (intra-firm) low-pay transitions using a multivariate Probit model that accounts for selection into low-wage employment and non-random employer drop-out. Using data from the LIAB Linked Employer-Employee panel, our results indicate that for male workers from the service sector the probability of escaping low-pay increases with employer size. This contrasts with female workers from the service sector, who rather benefit from collective bargaining coverage and local works councils. These findings are consistent with internal labour markets being an important ingredient of male within-firm wage growth, whereas the removal of asymmetric information appears to be more relevant in explaining female workers' wage transitions.
Keywords: C23; J31; J51; L13; 330; wage mobility; trivariate probit; linked employer-employee data; Niedriglohn; Erwerbsverlauf; Geschlecht; Interner Arbeitsmarkt; Betriebsrat; Betriebsgröße; Schätzung; Deutschland